1993
DOI: 10.1002/app.1993.070490507
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a polymeric additive in a biomedical poly(ether urethaneurea)

Abstract: SYNOPSISThe biomedical poly (ether urethaneurea) Biomer has previously been shown to contain a standard antioxidant and a polymethacrylate additive with surface active properties. In the present communication, the latter additive has been shown to influence the morphology, mechanical properties, and surface chemistry of a poly( ether urethaneurea) with a composition similar to Biomer. It was shown that the in uitro blood compatibility of the poly (ether urethaneurea) was improved and that adsorption of fibrino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…12,24 Santowhite Powder was cent increased after sterilization. The same effect also reported by Wu et al 32 to be present in was observed when the irradiation dose and the Biomer as an effective inhibitor surface cracking.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…12,24 Santowhite Powder was cent increased after sterilization. The same effect also reported by Wu et al 32 to be present in was observed when the irradiation dose and the Biomer as an effective inhibitor surface cracking.…”
Section: Resultsmentioning
confidence: 98%
“…23 by DSC may be attributed to the time scale of The additional relaxation peak in the tan d The EtO treatment seems to affect the additive, showing a decrease in the temperature of tan d curve at Ç 35ЊC exhibited by Biospan has been attributed to a polymethacrylate additive. 24 Other peak associated to it. studies of this additive have been reported.…”
Section: Resultsmentioning
confidence: 99%
“…In many of the applications where the excellent mechanical properties of PU are required, surface modification is expected to preserve the bulk properties. Indeed, the need to use a small amount of surface active compounds has been pointed out by Wesslén et al. ,, They have shown that the addition in small amounts (5% weight) of an amphiphilic polymer in polyurethanes and polyurethane ureas is sufficient to confer an amphiphilic nature to the material. These modifications keep the bulk properties unaltered.…”
Section: Introductionmentioning
confidence: 99%